Obituaries, newspaper cuttings, typescript speeches and commemorations relating to deceased members of the I.R.A. (S - W) - O'Donoghue, Florence, 1895-1967 (1946)
Material relates to Hanna Sheehy Skeffington (1946), Frank Thornton(Sept. 1965), Liam Twomey (Oct. 1964), Tadg Kenefick (Sept. 1922) and George P. Walsh.
Keywords: Irish Republican Army; Ireland -- History -- 1922-